2003
DOI: 10.1080/713609236
|View full text |Cite
|
Sign up to set email alerts
|

Group II Introns: Structure and Catalytic Versatility of Large Natural Ribozymes

Abstract: Group II introns are large, natural catalytic RNAs or ribozymes that were discovered in organelles of certain protists, fungi, algae, and plants and more recently also in prokaryotic organisms. In vitro, some members were found to self-splice from their pre-RNAs by two consecutive transesterification reactions joining the flanking exons and releasing the intron in a typical lariat form. Apart from self-splicing, a variety of other in vitro activities have been detected for group II introns demonstrating their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
136
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 303 publications
1
136
0
1
Order By: Relevance
“…The first step of splicing in this reaction apparently proceeds through hydrolysis rather than branching; however, catalysis of the first step of splicing through hydrolysis is widely observed in group II introns as a physiological alternative to branching both in vitro and in vivo (29,30). Indeed, under the conditions used in our catalytic assays, hydrolysis is the dominant or even the sole reaction pathway for a number of well-studied introns that can efficiently perform branching in the presence of higher salt concentrations (1,2). Recently, it has been shown that the spliceosomal active site can also catalyze hydrolytic reactions at splice sites by cleavage of the 2nd exon from lariat intermediates or spliced mRNAs (31).…”
Section: Discussionmentioning
confidence: 99%
“…The first step of splicing in this reaction apparently proceeds through hydrolysis rather than branching; however, catalysis of the first step of splicing through hydrolysis is widely observed in group II introns as a physiological alternative to branching both in vitro and in vivo (29,30). Indeed, under the conditions used in our catalytic assays, hydrolysis is the dominant or even the sole reaction pathway for a number of well-studied introns that can efficiently perform branching in the presence of higher salt concentrations (1,2). Recently, it has been shown that the spliceosomal active site can also catalyze hydrolytic reactions at splice sites by cleavage of the 2nd exon from lariat intermediates or spliced mRNAs (31).…”
Section: Discussionmentioning
confidence: 99%
“…[1] Some group II introns also encode for a maturase protein, enabling these RNAs to act as mobile genetic elements. [1] Although their direct occurrence is nowadays confined to a limited range of organisms, these catalytic RNAs may have played an important role in evolution. Taking into account related nuclear introns and transposable LINE elements, as much as one third of the human DNA may have evolved from ancestral group II introns.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In addition, based on reaction pathway and sequence similarity, a common ancestry with the eukaryotic spliceosomal machinery has been proposed. [1] The spliceosome is a multicomponent RNA-protein complex that occurs in higher eukaryotes and consists of five highly structured snRNAs (U1, U2, U4, U5 and U6) and numerous proteins, the latter ones presumably having structural roles. [3,4] Here, splicing occurs through the assembly of the snRNAs at pre-mRNA splice sites thereby exhibiting a mechanism that is very similar to the one found for group II introns.…”
Section: Introductionmentioning
confidence: 99%
“…the 2'-OH of a conserved adenosine, of these selfsplicing ribozymes, which exhibit a pathway strongly resembling the one of the 3 spliceosomal machinery. [18][19][20] Like all large ribozymes investigated to date, group II introns are obligate metalloribozymes that require Mg 2+ for folding and catalysis. [21][22][23][24][25][26][27] A recent crystal structure of a group IIC intron from Oceanobacillus iheyensis depicts the global architecture although domain 6 is disordered in the crystal.…”
mentioning
confidence: 99%